2020
DOI: 10.1021/acs.jpcc.9b11212
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Energy Storage Performance in Bilayer Composites Combining Aligned TiO2 Nanoarray and Random TiO2 Nanowires with Poly(vinylidene fluoride)

Abstract: TiO2 nanoarray (TNA) is usually used to improve the energy storage performance of the polymer composite; however, owing to the paradox between polarization and breakdown strength, the discharged energy density of TNA-based composite is always restricted. In this study, a novel bilayer composite with excellent energy storage performance has been designed and fabricated by combining aligned TNA and random TiO2 nanowires (TO NWs) with poly­(vinylidene fluoride) (PVDF) matrix. Interestingly, a superior discharged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Comparison of the current work’s energy density and charge–discharge efficiency with other reported works about sandwich-structured nanocomposites, which have the charge–discharge efficiency alongside large energy density. ,,,,,, …”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Comparison of the current work’s energy density and charge–discharge efficiency with other reported works about sandwich-structured nanocomposites, which have the charge–discharge efficiency alongside large energy density. ,,,,,, …”
Section: Resultsmentioning
confidence: 74%
“…8,13,23,31−33 Besides, various nanofillers, for instance, TiO 2 , SrTiO 3 , BaTiO 3 , and BN, to name some, are incorporated with the above-mentioned matrix materials to enhance the permittivity further and to some extent diverge the electric field treeing for realizing high energy density and efficient charge−discharge cycles. 5,8,34,35 Further, the ferroelectric-type polymer nanocomposites usually show high permittivity but greater conductive losses and lower charge−discharge efficiency. 36 On the other hand, linear-type polymer nanocomposites display the least losses but lower permittivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To make a more comprehensive comparison of the energy storage properties between inorganic filler/polymer matrix composites and the all-organic composite, relevant studies are shown in Figure . , The breakdown strength of the inorganic filler/polymer matrix composites is mostly concentrated below 550 kV mm –1 with a lower energy storage efficiency, as shown in Figure , which is greatly related to the defects generated by the introduction of inorganic fillers. The all-organic composite in this work can effectively avoid the generation of similar defects, achieve a higher breakdown strength, and maintain high efficiency, which makes it have a higher energy storage density although without a higher dielectric constant like inorganic filler/polymer matrix composites.…”
Section: Resultsmentioning
confidence: 99%
“…This result reveals that their system is a promising material for energy-storage applications. In addition, Ji et al [19] designed and fabricated a novel bilayer composite with an excellent energy-storage performance by combining an aligned TiO 2 nanoarray (TNA) and random TiO 2 nanowires (TiO 2 NWs) with a poly(vinylidene fluoride) (PVDF) matrix. A superior discharge energy density of 16.13 J cm −3 was obtained for the 5 vol% TiO 2 NW/TNA-PVDF composite, which was 2.0 times higher than that of the pure PVDF matrix (8.23 J cm −3 ).…”
Section: Introductionmentioning
confidence: 99%